2021
DOI: 10.1364/oe.434359
|View full text |Cite
|
Sign up to set email alerts
|

Perfectly-reflecting guided-mode-resonant photonic lattices possessing Mie modal memory

Abstract: Resonant periodic nanostructures provide perfect reflection across small or large spectral bandwidths depending on the choice of materials and design parameters. This effect has been known for decades, observed theoretically and experimentally via onedimensional and two-dimensional structures commonly known as resonant gratings, metamaterials, and metasurfaces. The physical cause of this extraordinary phenomenon is guided-mode resonance mediated by lateral Bloch modes excited by evanescent diffraction orders i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Despite the absence of narrow minima due to collective lattice resonances, their effect, nevertheless, manifests itself in a greater depth of the efficient broad minimum in the short-wavelength region of our spectra. This agrees to the results of 38 , which showed that the scattering maxima caused by lattice resonances can be located far from the strongest EM resonances of individual particles, which, in our case, are of the dipole type located in the region of relatively longer wavelengths.…”
Section: Numerical Simulationsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the absence of narrow minima due to collective lattice resonances, their effect, nevertheless, manifests itself in a greater depth of the efficient broad minimum in the short-wavelength region of our spectra. This agrees to the results of 38 , which showed that the scattering maxima caused by lattice resonances can be located far from the strongest EM resonances of individual particles, which, in our case, are of the dipole type located in the region of relatively longer wavelengths.…”
Section: Numerical Simulationsupporting
confidence: 93%
“…The study of the G -related effect was carried out for dimer-forming particles 34 , 35 and structures of several particles with different configurations 36 . The strongest interaction was observed in cases of collective lattice resonances 8 , 27 , 37 , 38 , which are well studied for plasmon resonances 17 , 37 . In case of dielectric particles, the collective lattice resonances are usually studied for structures with rather large G values.…”
Section: Introductionmentioning
confidence: 93%
“…Previous work showed that its minimum refractive index modulation speed was ∼10 ns, which was several orders of magnitude faster than the free-carrier effect . A more recent work demonstrated the modulation of a hybrid Mie-guided mode resonance via a tuning mechanism based on the quantum-confined Stark effect …”
Section: Active Materials and Tuning Mechanismsmentioning
confidence: 99%
“…For the sake of simplicity in analysis and potential fabrication, we consider a metasurface formed by a 1D grating of nanostripes of high-refractive-index material (for example, Si, GaP, and Ge) on the top of the magnetic film; however, similar results can be obtained for the nanoantennas of the other shapes. According to the Mie theory, such stripes produce resonances in the light scattering and absorption [ 32 , 33 ]. This scattered light experiences magneto-optical polarization rotation during its propagation through the magnetic film.…”
Section: Magnetophotonic Spin-wave Detection In Mie-based Metasurfacementioning
confidence: 99%